The Impact of Digital Marketing on Customers and Business Management in Commercial Enterprises and Profitability: Applied to Zain Telecommunications Company in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to evaluate the impact of digital marketing on customers and business management in Zain Telecommunications Company in the Kingdom of Saudi Arabia. The study sought to achieve several objectives, most notably: determining the effect of digital marketing on customer engagement and loyalty, evaluating the effectiveness of digital marketing strategies used, measuring the impact of digital marketing on operational efficiency and profitability, and studying its effect on customer behavior and satisfaction. The study adopted a descriptive analytical approach, using two main tools for data collection: a questionnaire for employees and another for customers. The study sample consisted of 82 employees and 163 customers of Zain Telecommunications. The researcher used a five-point Likert scale in designing the questionnaires to measure the study variables. The results of the study showed a statistically significant positive effect of digital marketing on customer engagement and loyalty to Zain. It also demonstrated the effectiveness of digital marketing strategies used in achieving the company's marketing objectives. The results also indicated a positive impact of digital marketing on the company's operational efficiency and profitability. Regarding customer behavior, the study showed that digital marketing has a significant influence on purchasing decisions and customer preferences. The study also recorded high levels of customer satisfaction and loyalty to Zain's brand in light of the applied digital marketing strategies. Based on these findings, the study recommended that Zain should continue to develop and continuously improve its digital marketing strategies. It also suggested increasing investment in modern digital technologies and training employees on the latest digital marketing techniques. Finally, the study recommended conducting periodic research to understand changing customer needs and adapt marketing strategies accordingly.
Keywords: Digital Marketing; Customer Preferences; Telecommunication Companies